Overcoming Cultural Barriers in Undergraduate Nursing Education Using Voice Enhanced High Fidelity Simulation: The Sultan Qaboos University Experience. Issue 2 (June 2019) - Matua, Gerald Amandu; Raghavan, Divya; Seshan, Vidya; Obeidat, Arwa Atef Sultan
No abstract available